Seroprevalence Trends and Molecular Epidemiology of Viral Hepatitis in Croatia - Tatjana Vilibic-Cavlek; Snjezana Zidovec-Lepej; Thomas Ferenc; Vladimir Savic; Tatjana Nemeth-Blazic; Mateja Vujica Ferenc; Maja Bogdanic; Maja Vilibic; Bojana Simunov; Natasa Janev-Holcer; Pavle Jelicic; Dominik Ljubas; et al. (Life, 2023)
Viral hepatitis is a significant cause of morbidity and mortality worldwide. In Croatia, hepatitis B virus (HBV) and hepatitis C virus (HCV) are widely distributed, especially in some high-risk groups such as people who inject drugs (PWID), prisoners, and highly promiscuous groups. The seroprevalence of HBV ranges from 7.0% in the general population to 38.8% in PWID, depending on the region. The seroprevalence of HCV is highest among PWID (29–75.5%) as compared to 0.9% in the general population. Analyzing the distribution of HCV genotypes, no substantial changes in the molecular epidemiology of the two most frequent HCV genotypes (1 and 3) in the past 20 years were observed. However, the predominance of subtype 1b compared to subtype 1a as detected in 1996–2005 was not confirmed in 2008–2015. Hepatitis A virus (HAV) incidence was high in the past with a decreasing trend since the 2000s, except for an outbreak in 2017–2018 as part of the large European outbreak, which was mainly among men who have sex with men. Hepatitis E virus (HEV) is an emerging virus detected for the first time in Croatia in 2012. The seroprevalence of HEV is high among hemodialysis patients (27.9%) and liver transplant recipients (19.3–24.4%). In addition, higher seroprevalence rates were observed in animal-related professions (e.g., veterinarians, 15.2%; hunters, 14.9%). All detected HEV strains belonged to genotype 3.